SOCIAL MEDIA CAPABILITIES AND MILITARY AFFAIRS USING PROPAGANDA AND TABAYYUN IN THE DIGITAL WARFARE - Dirgantara Hasibuan, Febri; Lazuardi, Afried (Lintas Cendekia Publishing, 2024)
This study explores the modern military theory to understand more regarding the revolution of social media in determining the narrative to win war in the digital warfare and the anticipation. What capabilities should the military hold to make sure the favorable outcome in the digital competitiveness environment. The anticipation of the narrative battle comes from the Islamic teaching tabayyun. The study used qualitative analysis as method, and collecting data through various text, video, sound and picture from the internet such as Facebook, Twitter, Youtube, Instagram and Tik Tok. The finding shows that propaganda is already in play in the traditional warfare. During this digital era, propaganda is used not only through main stream media, but also dominant in social media. Soldier should be battling not only in the physical battlefield but also in the virtual digital space. To answer those challenge, soldier should be equipped with a better tool, improving military tactics, techniques, and procedures in integrating social media capabilities. Also empowering individual soldiers and allowing small units to synchronize their action making every soldier a narrative agents and content creators.